Refractory hypokalemia and metabolic acidosis induced by undifferentiated connective tissue disease secondary to immune checkpoint inhibitors: a case report and literature review - Gu, Yinfang; Yi, Lilan; Zou, Xiaofang; Guo, Longhua; Wu, Guowu; Zhao, Jingjing (Frontiers in Oncology, 2024)
In the past, immune checkpoint inhibitors (ICIs) like camrelizumab have been associated with rheumatic immune-related adverse events (irAEs).To prevent serious adverse consequences, early diagnosis of rheumatic irAEs is crucial. A 40-year-old patient with malignant melanoma experienced severe hypokalemia and fatigue after 6 months of camrelizumab therapy, which was unresponsive to potassium chloride supplementation. Subsequently, the patient was diagnosed with refractory hypokalemia secondary to type I renal tubular acidosis (RTA). After treatment with potassium citrate and hydroxychloroquine, blood potassium, chloride, carbon dioxide binding capacity, and arterial blood gases returned to normal and the fatigue symptoms disappeared. However, severe hypokalemia and fatigue returned following resumption of camrelizumab therapy, and only resolved upon discontinuation and intensified symptomatic treatment. No recurrence of the condition was observed after camrelizumab was discontinued. Refractory hypokalemia and RTA were attributed to undifferentiated connective tissue disease (UCTD), a rheumatic condition considered as an adverse event of camrelizumab. This case underscores the necessity of monitoring serum potassium levels during ICI therapy and the consideration of RTA and autoimmune diseases in cases of hypokalemia to prevent serious adverse consequences.